A magnetic anchoring type ternary composite magnetic material and its preparation method and application

By preparing magnetically anchored ternary composite magnetic materials in a water environment, and using magnetic anchoring technology to improve material stability, the problem of insolid bonding of multi-composite materials in a water environment is solved, and the effect of efficient removal of organic dye pollutants is achieved.

CN119386838BActive Publication Date: 2025-05-02CHANGAN UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510006102.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-05-02
Estimated Expiration
2045-01-03

AI Technical Summary

Technical Problem

The combination of existing multi-component materials between monomer components in the aqueous environment is not firm and unstable, resulting in secondary environmental pollution after adsorbent saturation and difficulty in material recycling.

Method used

Nanoferrous tetraoxide-Schiff base binary composite magnetic material was prepared by in-situ polycondensation reaction, and the magnetic force between nanoferrous quadroxide and nanoferrous tetraoxide was used for anchoring to form a spherical three-layer core-shell structure of magnetic anchored ternary composite magnetic material.

Benefits of technology

The stability of the material in the water environment is improved, the defects of nano zero-valent iron agglomeration and Schiff base polymer dispersion are avoided, and the efficient adsorption and chemical reduction are achieved to remove organic dye pollutants, and it has good magnetic separation and low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119386838B_ABST
    Figure CN119386838B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of water environment restoration, and provides a magnetic anchoring type ternary composite magnetic material and its preparation method and application. The magnetic anchoring type ternary composite magnetic material obtained by the preparation method has a microstructure of a spherical three-layer core-shell structure, which includes a central inner layer, an intermediate coating layer and an outer inlay layer from the inside to the outside, the central inner layer is nano-ferroferric oxide, the intermediate coating layer is a micron-flaky Schiff base polymer, and the outer inlay layer is nano-zero-valent iron. In the magnetic anchoring type ternary composite magnetic material of the present invention, the nano-zero-valent iron in the outer layer is combined with the nano-ferroferric oxide in the center through magnetic force, which can ensure that the nano-ferroferric oxide, Schiff base polymer and nano-zero-valent iron in the ternary composite magnetic material are firmly combined, thereby improving the stability of the ternary composite magnetic material in the water environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of water environment restoration, and specifically relates to a magnetically anchored nano-ferroferric oxide-Schiff base-zero-valent iron ternary composite magnetic material (magnetically anchored ternary composite magnetic material) and a preparation method and application thereof. Background Art

[0002] Organic dyes in the water environment are difficult to degrade organic pollutants. They are highly carcinogenic and mutagenic to humans, and have growth inhibitory effects on both aquatic and terrestrial plants. Therefore, organic dyes pose a serious threat to the ecological environment and human health, and have been listed as "priority controlled pollutants." However, as important industrial products, organic dyes are mass-produced and widely used in various commercial fields. Currently, excessive amounts of organic dye pollutants have been monitored in surface and groundwater environments. How to efficiently remove organic dye pollutants in the water environment has become a difficulty and hot spot in the field of water environment remediation technology.

[0003] In recent years, researchers have developed a variety of water pollution control methods to treat organic dye pollutants in the water environment, mainly including microbial degradation, chemical precipitation, catalytic degradation, chemical oxidation, phytoremediation and adsorption. Compared with other methods, the adsorption method has the characteristics of convenient operation, high removal efficiency and wide application range, but the adsorption method only transfers organic dye pollutants from the water system to the adsorbent system. The adsorption saturated adsorbent is prone to cause secondary environmental pollution problems, and some adsorbent materials are highly dispersible and difficult to recover in the liquid matrix after the adsorption reaction. To this end, researchers have developed a multi-composite material, that is, a multi-composite material formed by combining components with adsorption and degradation. The multi-composite material can not only transfer organic dye pollutants from the water system to the adsorbent system, but also degrade the adsorbed organic dye pollutants, thereby avoiding secondary environmental pollution problems.

[0004] The stability of multi-component composite materials is one of the important parameters for evaluating their physicochemical properties. Generally speaking, the loading between monomer components in multi-component composite materials prepared by chemical reaction assembly methods is relatively firm and stable. However, the reaction systems of such chemical assembly methods mostly use toxic organic solvents as reaction reagents, and the reactions are complex and uncontrollable. The number and types of reactive sites are limited by the reaction conditions of the chemical reaction assembly methods. In multi-component composite materials prepared by physical assembly methods, the loading between monomer components is mostly achieved by intermolecular forces such as electrostatic micelle attraction or van der Waals force. However, the assembly between monomer components in such multi-component composite materials is not firm, and the separation of monomer components can easily cause secondary environmental pollution problems. Summary of the invention

[0005] Aiming at the defects of weak and unstable bonding between monomer components of multi-component composite materials in the prior art, the present invention provides a magnetic anchoring type ternary composite magnetic material and a preparation method and application thereof.

[0006] The present invention is achieved through the following technical solutions:

[0007] A method for preparing a magnetic anchoring ternary composite magnetic material comprises the following steps:

[0008] S1, dispersing nano-ferroferric oxide in ethanol to obtain a nano-ferroferric oxide dispersion; dissolving an amine compound in ethanol to obtain an amine solution; dissolving an aldehyde compound in ethanol to obtain an aldehyde solution;

[0009] S2, adding the amine solution and the aldehyde solution to the nano-ferroferric oxide dispersion, reacting under stirring conditions, separating the precipitate after the reaction is completed, washing and drying to obtain the nano-ferroferric oxide-Schiff base binary composite magnetic material;

[0010] S3, dispersing nano-ferroferric oxide-Schiff base binary composite magnetic material in ethanol to obtain a binary composite magnetic material solution; dispersing nano-zero-valent iron in ethanol to obtain a nano-zero-valent iron solution; adding the nano-zero-valent iron solution dropwise into the binary composite magnetic material solution under stirring conditions, separating the precipitate after continuous stirring, washing and drying to obtain a magnetically anchored ternary composite magnetic material.

[0011] Preferably, in S1, the preparation method of nano-iron tetroxide comprises: dissolving FeCl3 in a mixed solution of water, ethanol, n-hexane and oleic acid, and reacting under stirring conditions; adding sodium hydroxide to the obtained reaction solution, reacting under heating and stirring conditions, separating the liquid after the reaction is completed, washing and drying the organic layer obtained by the separation to obtain an organic mixture; dispersing the organic mixture in a mixed solvent of oleic acid and 1-octadecene, reacting under a nitrogen atmosphere and heating conditions, and after the reaction is completed, washing and drying to obtain nano-iron tetroxide.

[0012] Preferably, in S1, the amine compound is o-tolidine or diphenylamine, and the aldehyde compound is terephthalaldehyde or 4,4'-biphenyldicarboxaldehyde.

[0013] Preferably, in S2, the amine solution and the aldehyde solution are added to the nano-ferroferric oxide dispersion according to the molar ratio of the amine compound, the aldehyde compound and the nano-ferroferric oxide of 1:1:(6-8).

[0014] Preferably, in S3, the mass ratio of nano-iron tetroxide-Schiff base binary composite magnetic material to nano-zero-valent iron is (0.18-0.11): (0.02-0.09).

[0015] Preferably, in S3, the method for preparing nano zero-valent iron comprises: dissolving ferric chloride in a mixed solution of ethanol and water, then adding a potassium borohydride solution dropwise to the mixed solution, reacting under stirring conditions, and after the reaction is completed, separating the precipitate and washing and drying it to obtain nano zero-valent iron.

[0016] Preferably, in S3, stirring is performed under anaerobic conditions.

[0017] Preferably, in S3, separating the precipitate comprises separating the precipitate by magnetic separation.

[0018] The present invention also provides a magnetically anchored ternary composite magnetic material obtained by the preparation method. The microstructure of the magnetically anchored ternary composite magnetic material is a spherical three-layer core-shell structure, which includes, from the inside to the outside, a central inner layer, an intermediate coating layer and an outer inlay layer. The central inner layer is nano-ferroferric oxide, the intermediate coating layer is a micron-flaky Schiff base polymer, and the outer inlay layer is nano-zero-valent iron.

[0019] The present invention also provides application of the magnetic anchoring type ternary composite magnetic material in removing organic dye pollutants in water.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] The present invention firstly utilizes an in-situ polycondensation reaction to coat a Schiff base polymer on the outer surface of nano-iron tetroxide, and prepares a nano-iron tetroxide-Schiff base binary composite magnetic material with a core-shell structure. The Schiff base polymer is coated on the outer surface of the central inner layer formed by the nano-iron tetroxide in a micron-sheet structure, and then the nano-zero-valent iron material is firmly loaded on the outer surface of the nano-iron tetroxide-Schiff base binary composite magnetic material by utilizing the magnetic force between the nano-zero-valent iron and the nano-iron tetroxide, and finally a magnetic anchored nano-iron tetroxide-Schiff base-zero-valent iron ternary composite magnetic material with a spherical overall morphology and a three-layer core-shell structure is prepared, i.e., a magnetic anchored ternary composite magnetic material. That is, the present invention utilizes the inherent magnetic force of nano-iron tetroxide to assemble the Schiff base polymer and the nano-zero-valent iron together. Magnetic force is a stable and strong force. In the magnetic anchored ternary composite magnetic material of the present invention, the nanometer zero-valent iron in the outer layer is combined with the nanometer ferroferric oxide in the center through magnetic force, which can ensure that the nanometer ferroferric oxide, Schiff base polymer and nanometer zero-valent iron in the magnetic anchored ternary composite magnetic material are firmly combined, thereby improving the stability of the magnetic anchored ternary composite magnetic material in the water environment. At the same time, the present invention avoids the defect that nanometer zero-valent iron is easy to agglomerate in the solution system and the defect that Schiff base polymer is easy to disperse in the solution system by forming a magnetic anchored ternary composite magnetic material. Since the formation of magnetic force only relies on the inherent magnetic characteristics of the magnetic material and does not require the help of complex physical and chemical reactions, the preparation process of the magnetic anchored ternary composite magnetic material of the present invention is simple. In the magnetic anchoring ternary composite magnetic material of the present invention, the Schiff base polymer is rich in aromatic carbon, and is easy to form π-π interaction force, electron donor-acceptor interaction force and van der Waals force with organic dyes and their reduction products, which is beneficial to the efficient adsorption of organic dye pollutants. Nano zero-valent iron has strong reducing property, and can reduce and remove the adsorbed organic dye pollutants. Therefore, the magnetic anchoring ternary composite magnetic material of the present invention realizes the cascade removal reaction effect of chemical reduction and synergistic adsorption, shows excellent removal performance for organic dye pollutants, and has strong magnetic separation and low cost. Compared with other composite materials, it has good application prospects.

[0022] Furthermore, the present invention optimizes the types of aldehydes and amines on the Schiff base polymer, and can achieve the preparation of high-performance magnetic anchoring ternary composite magnetic materials.

[0023] Furthermore, the present invention optimizes the molar ratio of the Schiff base polymer and the nano-zero-valent iron, which can ensure that the magnetic anchoring ternary composite magnetic material has sufficient reactive active sites.

[0024] Furthermore, the present invention optimizes the appropriate amount of nano zero-valent iron added, which can achieve a good reduction and removal effect on organic dye pollutants without affecting the adsorption of Schiff base polymers.

[0025] Furthermore, the nano-ferroferric oxide-Schiff base binary composite magnetic material of the present invention is composited with nano-zero-valent iron under anaerobic conditions, thereby avoiding the risk of oxidation of the nano-zero-valent iron.

[0026] The magnetic anchoring ternary composite magnetic material of the present invention is a three-layer core-shell structure, which includes a central inner layer, an intermediate coating layer and an outer inlay layer from the inside to the outside, wherein the central inner layer is nano-ferroferric oxide, the intermediate coating layer is a Schiff base polymer, and the outer inlay layer is nano-zero-valent iron. The nano-zero-valent iron in the outer layer is combined with the nano-ferroferric oxide in the interior by magnetic force, and the magnetic force is a stable and strong force. Therefore, the nano-ferroferric oxide, Schiff base polymer, and nano-zero-valent iron in the magnetic anchoring ternary composite magnetic material of the present invention are firmly combined, thereby improving the stability of the ternary composite magnetic material in an aqueous environment. At the same time, the present invention avoids the defect that nano-zero-valent iron is easy to agglomerate in a solution system and avoids the defect that Schiff base polymer is easy to disperse in a solution system by forming a magnetic anchoring ternary composite magnetic material. In addition, in the magnetically anchored ternary composite magnetic material of the present invention, the Schiff base polymer easily forms π-π interaction forces, electron donor-acceptor interaction forces and van der Waals forces with the organic dye and its reduction products, which is beneficial to the efficient removal of organic dye pollutants. Nano zero-valent iron has strong reducing properties and can reduce and remove the adsorbed organic dye pollutants, showing excellent removal performance for organic dye pollutants. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0028] Figure 1 This is a scanning electron microscope image of the nano-iron tetroxide material prepared in Example 1.

[0029] Figure 2 This is a scanning electron microscope image of the nano-iron tetroxide-Schiff base binary composite magnetic material prepared in Example 1.

[0030] Figure 3 This is a scanning electron microscope image of the magnetically anchored ternary composite magnetic material prepared in Example 1.

[0031] Figure 4 This is a scanning electron microscope image of the Schiff base-zero-valent iron binary composite magnetic material prepared in Comparative Example 3.

[0032] Figure 5 Schematic diagram of magnetic separation of solutions of the magnetically anchored ternary composite magnetic material prepared in Example 1 and the Schiff base-zero-valent iron binary composite magnetic material prepared in Comparative Example 3 after ultrasonic treatment; (A) is the magnetically anchored ternary composite magnetic material; (B) is the Schiff base-zero-valent iron binary composite magnetic material.

[0033] Figure 6 A comparison chart of the removal performance of methyl orange pollutants by the magnetic anchoring ternary composite magnetic material (with different nano zero-valent iron loadings) prepared by the present invention (i.e., Application Examples 1, 3, 5, 7, 9, 11, 13 and 15).

[0034] Figure 7 The present invention provides a comparative chart of the removal performance of methyl orange pollutants by ternary composite magnetic materials prepared with different molar ratios of amine compounds, aldehyde compounds and nano-ferroferric oxide, ternary composite magnetic materials prepared with different types of aldehyde compounds and amine compounds, nano-ferroferric oxide-Schiff base binary composite magnetic materials and nano-zero-valent iron monomer materials (i.e., Application Examples 1, 17, 19, 21, 23, 25, 27 and 29).

[0035] Figure 8 A comparison chart of the removal performance of the magnetic anchored ternary composite magnetic material (with different nano zero-valent iron loadings) prepared by the present invention for Rhodamine B pollutants (i.e., Application Examples 2, 4, 6, 8, 10, 12, 14 and 16).

[0036] Fig. 9 The present invention provides a comparative chart of the removal performance of rhodamine B pollutants by ternary composite magnetic materials prepared with different molar ratios of amine compounds, aldehyde compounds and nano-ferroferric oxide, composite magnetic materials prepared with different types of aldehyde compounds and amine compounds, nano-ferroferric oxide-Schiff base binary composite magnetic materials and nano zero-valent iron monomer materials (i.e., Application Examples 2, 18, 20, 22, 24, 26, 28 and 30). DETAILED DESCRIPTION

[0037] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.

[0038] It should be noted that the process equipment or devices not specifically specified in the following embodiments are all conventional equipment or devices in the art.

[0039] It should be noted that the terms "include" and "have" and any variations thereof are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices. Moreover, unless otherwise specified, the numbering of each method step is only a convenient tool for identifying each method step, and is not intended to limit the order of arrangement of each method step or to define the scope of the present invention. Changes or adjustments in their relative relationships should also be regarded as the scope of the present invention without substantially changing the technical content.

[0040] The method for preparing the magnetic anchoring ternary composite magnetic material of the present invention comprises the following steps:

[0041] S1, dispersing nano-ferroferric oxide in ethanol to obtain a nano-ferroferric oxide dispersion; dissolving an amine compound in ethanol to obtain an amine solution; dissolving an aldehyde compound in ethanol to obtain an aldehyde solution;

[0042] S2, adding the amine solution and the aldehyde solution to the nano-ferroferric oxide dispersion, reacting under stirring conditions, separating the precipitate after the reaction is completed, washing and drying to obtain the nano-ferroferric oxide-Schiff base binary composite magnetic material;

[0043] S3, dispersing nano-ferroferric oxide-Schiff base binary composite magnetic material in ethanol to obtain a binary composite magnetic material solution; dispersing nano-zero-valent iron in ethanol to obtain a nano-zero-valent iron solution; adding the nano-zero-valent iron solution dropwise into the binary composite magnetic material solution under stirring conditions, separating the precipitate after continuous stirring, washing and drying to obtain a magnetically anchored ternary composite magnetic material.

[0044] The preparation method of the magnetic anchoring ternary composite magnetic material of the present invention adopts a preparation method of nano-iron tetroxide, which includes: dissolving FeCl3 in a mixed solution of water, ethanol, n-hexane and oleic acid, and reacting under stirring conditions; adding sodium hydroxide to the obtained reaction solution, reacting under heating and stirring conditions, separating the liquid after the reaction is completed, washing and drying the organic layer obtained by the separation to obtain an organic mixture; dispersing the organic mixture in a mixed solvent of oleic acid and 1-octadecene, reacting under a nitrogen atmosphere and heating conditions, and washing and drying after the reaction is completed to obtain nano-iron tetroxide.

[0045] In the method for preparing nano-ferroferric tetroxide, after the reaction of the organic mixture is completed, the washing process is specifically as follows: cooling and dispersing in ethanol for precipitation, collecting the precipitate; dispersing the precipitate in n-hexane, precipitating again with ethanol, and repeating the dispersion and precipitation steps multiple times to improve the purity of the nano-ferroferric tetroxide. Preferably, the dispersion and precipitation steps are repeated 3-5 times.

[0046] In the preparation method of the magnetic anchoring ternary composite magnetic material of the present invention, the amine compound is o-tolidine or diphenylamine, and the aldehyde compound is terephthalaldehyde or 4,4'-biphenyldicarboxaldehyde.

[0047] The preparation method of the nano zero-valent iron adopted in the preparation method of the magnetic anchoring ternary composite magnetic material of the present invention comprises: dissolving ferric chloride in a mixed solution of ethanol and water, then adding potassium borohydride solution to the mixed solution at a rate of 20-30 drops / minute, reacting under stirring conditions, and after the reaction is completed, separating out a black precipitate, and then washing and drying to obtain nano zero-valent iron.

[0048] In the method for preparing nano zero-valent iron, it is preferred to use anhydrous ethanol and oxygen-free deionized water to wash the black precipitate 3-5 times.

[0049] In S3 of the present invention, the nano zero-valent iron solution is preferably added to the binary composite magnetic material solution at a speed of 20-30 drops / minute. Here, the slow drop loading method can effectively avoid the occurrence of nano zero-valent iron agglomeration. If the drop acceleration is too fast, the nano zero-valent iron cannot be evenly anchored on the outer surface of the binary composite magnetic material and is easy to aggregate with each other. After the above reaction is completed, the precipitate is separated by magnetic separation and washed with anhydrous ethanol for 3-5 times.

[0050] In S2 of the present invention, the amine solution and the aldehyde solution are added into the nano-ferroferric oxide dispersion according to the molar ratio of the amine compound, the aldehyde compound and the nano-ferroferric oxide of 1:1:(6-8).

[0051] In S3 of the present invention, the mass ratio of nano-ferroferric oxide-Schiff base binary composite magnetic material to nano-zero-valent iron is (0.18-0.11): (0.02-0.09). The amount of nano-zero-valent iron added has a certain influence on the performance of the final material. When the amount added is too low, it cannot play a good reduction and removal role on organic dye pollutants. When the amount added is too high, it will affect the Schiff base polymer, which is not conducive to the adsorption of the Schiff base polymer and the organic dye pollutants. The present invention optimizes the appropriate amount of nano-zero-valent iron added, which can achieve a good reduction and removal effect on organic dye pollutants without affecting the adsorption of the Schiff base polymer.

[0052] In the present invention, the dispersion is achieved by ultrasonic dispersion.

[0053] Example 1

[0054] This embodiment provides a method for preparing a magnetic anchoring ternary composite magnetic material, comprising:

[0055] Step (1): 1 mmol FeCl3 is dissolved in a mixed solution of 3 mL deionized water, 4 mL ethanol, 7 mL n-hexane and 1 mL oleic acid, and the mixture is stirred and reacted for 0.5 h at room temperature; then 0.12 g sodium hydroxide is added to the mixed solution, the mixture is sealed, and the mixture is stirred and reacted at 70 °C for 4 h. After the reaction is completed, the organic layer is separated and collected using a separatory funnel, the collected organic layer is washed with distilled water, and dried at 60 °C for 24 h to obtain a viscous organic mixture; then the viscous organic mixture is dispersed in a mixed solvent of 0.16 mL oleic acid and 6.5 mL 1-octadecene, the solution is purged with nitrogen for 30 min, and then reacted in a nitrogen atmosphere at 320 °C for 0.5 h. After cooling, excess ethanol is added for precipitation and a precipitate is obtained. The precipitate is dispersed in n-hexane again and precipitated with ethanol. The dispersion and precipitation steps are repeated 5 times, and then the obtained solid is vacuum dried at 60 °C for 48 h to obtain nano-iron tetroxide.

[0056] Step (2): Disperse 0.325 g of nano-iron tetroxide in 100 mL of ethanol and ultrasonically treat for 10 min to obtain a nano-iron tetroxide dispersion; dissolve 0.0498 g of o-tolidine in 150 mL of ethanol to obtain an amine solution; dissolve 0.0315 g of terephthalaldehyde in 150 mL of ethanol to obtain an aldehyde solution. Then add the amine solution and the aldehyde solution to the nano-iron tetroxide dispersion, place the obtained mixed solution on a mechanical stirrer and stir it continuously at room temperature for 24 h, separate a yellow-black precipitate, then wash the yellow-black precipitate with anhydrous ethanol 5 times, and vacuum dry it at 60 ° C for 24 h to obtain a nano-iron tetroxide-Schiff base binary composite magnetic material.

[0057] Step (3): 0.3 g of ferric chloride was dissolved in a mixed solution of 100 mL of ethanol and 50 mL of deionized water, and then 40 mL of potassium borohydride solution was slowly added to the mixed solution at a rate of 20 drops / min. The mixture was mechanically stirred for 2 h, and the black precipitate was magnetically separated. The precipitate was washed 5 times with anhydrous ethanol and oxygen-free deionized water, and then vacuum dried at 60 °C for 24 h to obtain a nano zero-valent iron sample.

[0058] Step (4): 0.11 g of the nano-iron tetroxide-Schiff base binary composite magnetic material prepared in step (2) is dispersed in 200 mL of ethanol to obtain a binary composite magnetic material solution; 0.09 g of the nano-zero-valent iron prepared in step (3) is ultrasonically dispersed in 100 mL of ethanol, and then the ethanol dispersed with the nano-zero-valent iron is added dropwise to the binary composite magnetic material solution at a rate of 20 drops / minute, and mechanical stirring is continued for 2 h. The reaction system is kept in an anaerobic condition, and then magnetic separation is performed and washed with anhydrous ethanol for 5 times, and vacuum dried at 60°C for 24 h to obtain a magnetically anchored ternary composite magnetic material.

[0059] Example 2

[0060] The present embodiment provides a method for preparing a magnetically anchored ternary composite magnetic material. The specific preparation process is similar to that of the embodiment 1, except for step (4): 0.12 g of the nano-iron tetroxide-Schiff base binary composite magnetic material prepared in step (2) is dispersed in 200 mL of ethanol to obtain a binary composite magnetic material solution; 0.08 g of the nano-zero-valent iron prepared in step (3) is ultrasonically dispersed in 100 mL of ethanol, and then the ethanol dispersed with the nano-zero-valent iron is added dropwise to the binary composite magnetic material solution at a rate of 20 drops / min, and mechanical stirring is continued for 2 h. The reaction system is kept in an anaerobic condition, and then magnetic separation is performed and the mixture is washed with anhydrous ethanol for 5 times, and vacuum dried at 60°C for 24 h to obtain a magnetically anchored ternary composite magnetic material.

[0061] Example 3

[0062] The present embodiment provides a method for preparing a magnetically anchored ternary composite magnetic material. The specific preparation process is similar to that of the embodiment 1, except for step (4): 0.13 g of the nano-iron tetroxide-Schiff base binary composite magnetic material prepared in step (2) is dispersed in 200 mL of ethanol to obtain a binary composite magnetic material solution; 0.07 g of the nano-zero-valent iron prepared in step (3) is ultrasonically dispersed in 100 mL of ethanol, and then the ethanol dispersed with the nano-zero-valent iron is added dropwise to the binary composite magnetic material solution at a rate of 20 drops / min, and mechanical stirring is continued for 2 h. The reaction system is kept in an anaerobic condition, and then magnetic separation is performed and the mixture is washed with anhydrous ethanol for 5 times, and vacuum dried at 60°C for 24 h to obtain a magnetically anchored ternary composite magnetic material.

[0063] Example 4

[0064] The present embodiment provides a method for preparing a magnetically anchored ternary composite magnetic material. The specific preparation process is similar to that of the embodiment 1, except for step (4): 0.14 g of the nano-iron tetroxide-Schiff base binary composite magnetic material prepared in step (2) is dispersed in 200 mL of ethanol to obtain a binary composite magnetic material solution; 0.06 g of the nano-zero-valent iron prepared in step (3) is ultrasonically dispersed in 100 mL of ethanol, and then the ethanol dispersed with the nano-zero-valent iron is added dropwise to the binary composite magnetic material solution at a rate of 20 drops / min, and mechanical stirring is continued for 2 h. The reaction system is kept in an anaerobic condition, and then magnetic separation is performed and the mixture is washed with anhydrous ethanol for 5 times, and vacuum dried at 60°C for 24 h to obtain a magnetically anchored ternary composite magnetic material.

[0065] Example 5

[0066] The present embodiment provides a method for preparing a magnetically anchored ternary composite magnetic material. The specific preparation process is similar to that of Embodiment 1, except for step (4): 0.15 g of the nano-iron tetroxide-Schiff base binary composite magnetic material prepared in step (2) is dispersed in 200 mL of ethanol to obtain a binary composite magnetic material solution; 0.05 g of the nano-zero-valent iron prepared in step (3) is ultrasonically dispersed in 100 mL of ethanol, and then the ethanol dispersed with the nano-zero-valent iron is added dropwise to the binary composite magnetic material solution at a rate of 20 drops / min, and mechanical stirring is continued for 2 h. The reaction system is kept in an anaerobic condition, and then magnetic separation is performed and the mixture is washed with anhydrous ethanol for 5 times, and vacuum dried at 60°C for 24 h to obtain a magnetically anchored ternary composite magnetic material.

[0067] Example 6

[0068] The present embodiment provides a method for preparing a magnetically anchored ternary composite magnetic material. The specific preparation process is similar to that of the embodiment 1, except for step (4): 0.16 g of the nano-iron tetroxide-Schiff base binary composite magnetic material prepared in step (2) is dispersed in 200 mL of ethanol to obtain a binary composite magnetic material solution; 0.04 g of the nano-zero-valent iron prepared in step (3) is ultrasonically dispersed in 100 mL of ethanol, and then the ethanol dispersed with the nano-zero-valent iron is added dropwise to the binary composite magnetic material solution at a rate of 20 drops / min, and mechanical stirring is continued for 2 h. The reaction system is kept in an anaerobic condition, and then magnetic separation is performed and the mixture is washed with anhydrous ethanol for 5 times, and vacuum dried at 60°C for 24 h to obtain a magnetically anchored ternary composite magnetic material.

[0069] Example 7

[0070] The present embodiment provides a method for preparing a magnetically anchored ternary composite magnetic material. The specific preparation process is similar to that of Embodiment 1, with the only difference being step (4): dispersing 0.17 g of the nano-iron tetroxide-Schiff base binary composite magnetic material prepared in step (2) in 200 mL of ethanol to obtain a binary composite magnetic material solution; ultrasonically dispersing 0.03 g of the nano-zero-valent iron prepared in step (3) in 100 mL of ethanol, and then dripping the ethanol dispersed with the nano-zero-valent iron into the binary composite magnetic material solution at a rate of 20 drops / min, and continuously mechanically stirring for 2 h. The reaction system is kept in an anaerobic condition, and then magnetic separation is performed and the mixture is washed with anhydrous ethanol for 5 times, and vacuum dried at 60°C for 24 h to obtain a magnetically anchored ternary composite magnetic material.

[0071] Example 8

[0072] The present embodiment provides a method for preparing a magnetically anchored ternary composite magnetic material. The specific preparation process is similar to that of Embodiment 1, except for step (4): 0.18 g of the nano-iron tetroxide-Schiff base binary composite magnetic material prepared in step (2) is dispersed in 200 mL of ethanol to obtain a binary composite magnetic material solution; 0.02 g of the nano-zero-valent iron prepared in step (3) is ultrasonically dispersed in 100 mL of ethanol, and then the ethanol dispersed with the nano-zero-valent iron is added dropwise to the binary composite magnetic material solution at a rate of 20 drops / min, and mechanical stirring is continued for 2 h. The reaction system is kept in an anaerobic condition, and then magnetic separation is performed and the mixture is washed with anhydrous ethanol for 5 times, and vacuum dried at 60°C for 24 h to obtain a magnetically anchored ternary composite magnetic material.

[0073] Example 9

[0074] The present embodiment provides a method for preparing a magnetically anchored ternary composite magnetic material. The specific preparation process is similar to that of Example 1, except that the 0.325 g of nano-ferroferric oxide in step (2) is replaced by 0.373 g of nano-ferroferric oxide (the molar ratio of the amine compound, the aldehyde compound and the nano-ferroferric oxide is 1:1:7).

[0075] Example 10

[0076] The present embodiment provides a method for preparing a magnetically anchored ternary composite magnetic material. The specific preparation process is similar to that of Example 1, except that the 0.325 g of nano-ferroferric oxide in step (2) is replaced by 0.428 g of nano-ferroferric oxide (the molar ratio of the amine compound, the aldehyde compound and the nano-ferroferric oxide is 1:1:8).

[0077] Embodiment 11

[0078] This embodiment provides a method for preparing a magnetic anchoring ternary composite magnetic material. The specific preparation process is similar to that of Example 1, except that the o-tolidine in step (2) is replaced by 0.0421 g of dibenzhydrylamine.

[0079] Example 12

[0080] This embodiment provides a method for preparing a magnetic anchoring ternary composite magnetic material. The specific preparation process is similar to that of Example 1, except that the terephthalaldehyde in step (2) is replaced by 0.0484 g of 4,4'-biphenyldicarboxaldehyde.

[0081] Comparative Example 1

[0082] According to steps (1) and (2) of Example 1, a nano-iron tetroxide-Schiff base binary composite magnetic material is obtained.

[0083] Comparative Example 2

[0084] The nanometer zero-valent iron material was obtained by following step (3) of Example 1.

[0085] Comparative Example 3

[0086] This comparative example provides a method for preparing a Schiff base-zero-valent iron binary composite magnetic material, comprising:

[0087] Step (1): 0.0498 g of o-tolidine is dissolved in 150 mL of ethanol to obtain an amine solution; 0.0315 g of terephthalaldehyde is dissolved in 150 mL of ethanol to obtain an aldehyde solution; the amine solution and the aldehyde solution are then mixed, and the mixture is reacted under mechanical stirring for 24 h, a precipitate is separated, and the precipitate is then washed with anhydrous ethanol for 5 times, and vacuum dried at 60 ° C for 24 h to obtain a Schiff base polymer.

[0088] Step (2): 0.3 g of ferric chloride was dissolved in a mixed solution of 100 mL of ethanol and 50 mL of deionized water, and then 40 mL of potassium borohydride solution was slowly added to the mixed solution at a rate of 20 drops / min. The mixture was mechanically stirred for 2 h, and the black precipitate was magnetically separated. The precipitate was washed 5 times with anhydrous ethanol and oxygen-free deionized water, and then vacuum dried at 60 ° C for 24 h to obtain a nano zero-valent iron sample.

[0089] Step (3): 0.035 g of Schiff base polymer and hexadecyltrimethylammonium bromide were dissolved in 200 mL of ethanol and mechanically stirred for 0.5 h at room temperature to obtain a Schiff base solution; 0.06 g of nano-zero-valent iron was ultrasonically dispersed in 100 mL of ethanol, and then the ethanol dispersed with nano-zero-valent iron was added to the Schiff base solution at a rate of 20 drops / min, and mechanical stirring was continued for 2 h. The reaction system was kept in an anaerobic condition, and then magnetic separation was performed and washed with anhydrous ethanol for 5 times, and vacuum dried at 60 ° C for 24 h to obtain a Schiff base-zero-valent iron binary composite magnetic material.

[0090] Application Example 1

[0091] At room temperature, 0.02 g of the magnetic anchoring ternary composite magnetic material prepared in Example 1 was added to a stoppered brown conical flask. 100 mL of a 20 mg / L methyl orange solution was added to the conical flask, and the pH value of the reaction system was adjusted to about 5 using 1 mol / L hydrochloric acid. The conical flask was placed on a temperature-controlled shaker at 30 °C for 3 h, and the concentration of the supernatant of the reaction system was measured to analyze the removal efficiency of the magnetic anchoring ternary composite magnetic material for methyl orange pollutants.

[0092] Application Example 2

[0093] This application example is similar to application example 1, except that the methyl orange solution is replaced by a rhodamine B solution.

[0094] Application Example 3

[0095] This application example is similar to application example 1, except that 0.02 g of the magnetic anchoring ternary composite magnetic material prepared in Example 1 is replaced with 0.02 g of nano-ferroferric oxide-Schiff base-zero-valent iron ternary composite magnetic material prepared in Example 2.

[0096] Application Example 4

[0097] This application example is similar to application example 3, except that the methyl orange solution is replaced by a rhodamine B solution.

[0098] Application Example 5

[0099] This application example is similar to application example 1, except that 0.02 g of the magnetic anchoring ternary composite magnetic material prepared in Example 1 is replaced with 0.02 g of nano-ferroferric oxide-Schiff base-zero-valent iron ternary composite magnetic material prepared in Example 3.

[0100] Application Example 6

[0101] This application example is similar to application example 5, except that the methyl orange solution is replaced by a rhodamine B solution.

[0102] Application Example 7

[0103] This application example is similar to application example 1, except that 0.02 g of the magnetic anchoring ternary composite magnetic material prepared in Example 1 is replaced with 0.02 g of nano-ferroferric oxide-Schiff base-zero-valent iron ternary composite magnetic material prepared in Example 4.

[0104] Application Example 8

[0105] This application example is similar to application example 7, except that the methyl orange solution is replaced by a rhodamine B solution.

[0106] Application Example 9

[0107] This application example is similar to application example 1, except that 0.02 g of the magnetic anchoring ternary composite magnetic material prepared in Example 1 is replaced with 0.02 g of nano-ferroferric oxide-Schiff base-zero-valent iron ternary composite magnetic material prepared in Example 5.

[0108] Application Example 10

[0109] This application example is similar to application example 9, except that the methyl orange solution is replaced by a rhodamine B solution.

[0110] Application Example 11

[0111] This application example is similar to application example 1, except that 0.02 g of the magnetic anchoring ternary composite magnetic material prepared in Example 1 is replaced with 0.02 g of nano-ferroferric oxide-Schiff base-zero-valent iron ternary composite magnetic material prepared in Example 6.

[0112] Application Example 12

[0113] This application example is similar to application example 11, except that the methyl orange solution is replaced by a rhodamine B solution.

[0114] Application Example 13

[0115] This application example is similar to application example 1, except that 0.02 g of the magnetic anchoring ternary composite magnetic material prepared in Example 1 is replaced with 0.02 g of nano-ferroferric oxide-Schiff base-zero-valent iron ternary composite magnetic material prepared in Example 7.

[0116] Application Example 14

[0117] This application example is similar to application example 13, except that the methyl orange solution is replaced by a rhodamine B solution.

[0118] Application Example 15

[0119] This application example is similar to application example 1, except that 0.02 g of the magnetic anchoring ternary composite magnetic material prepared in Example 1 is replaced with 0.02 g of nano-ferroferric oxide-Schiff base-zero-valent iron ternary composite magnetic material prepared in Example 8.

[0120] Application Example 16

[0121] This application example is similar to application example 15, except that the methyl orange solution is replaced by a rhodamine B solution.

[0122] Application Example 17

[0123] This application example is similar to application example 1, except that 0.02 g of the magnetic anchoring ternary composite magnetic material prepared in Example 1 is replaced with 0.02 g of nano-ferroferric oxide-Schiff base-zero-valent iron ternary composite magnetic material prepared in Example 9.

[0124] Application Example 18

[0125] This application example is similar to application example 17, except that the methyl orange solution is replaced by a rhodamine B solution.

[0126] Application Example 19

[0127] This application example is similar to application example 1, except that 0.02 g of the magnetic anchoring ternary composite magnetic material prepared in Example 1 is replaced with 0.02 g of nano-ferroferric oxide-Schiff base-zero-valent iron ternary composite magnetic material prepared in Example 10.

[0128] Application Example 20

[0129] This application example is similar to application example 19, except that the methyl orange solution is replaced by a rhodamine B solution.

[0130] Application Example 21

[0131] This application example is similar to application example 1, except that 0.02 g of the magnetic anchoring ternary composite magnetic material prepared in Example 1 is replaced with 0.02 g of nano-ferroferric oxide-Schiff base-zero-valent iron ternary composite magnetic material prepared in Example 11.

[0132] Application Example 22

[0133] This application example is similar to application example 21, except that the methyl orange solution is replaced by a rhodamine B solution.

[0134] Application Example 23

[0135] This application example is similar to application example 1, except that 0.02 g of the magnetic anchoring ternary composite magnetic material prepared in Example 1 is replaced with 0.02 g of nano-ferroferric oxide-Schiff base-zero-valent iron ternary composite magnetic material prepared in Example 12.

[0136] Application Example 24

[0137] This application example is similar to application example 23, except that the methyl orange solution is replaced by a rhodamine B solution.

[0138] Application Example 25

[0139] This application example is similar to application example 1, except that 0.02 g of the magnetic anchoring ternary composite magnetic material prepared in Example 1 is replaced with 0.011 g of the nano-iron tetroxide-Schiff base binary composite magnetic material of Comparative Example 1.

[0140] Application Example 26

[0141] This application example is similar to application example 25, except that the methyl orange solution is replaced by a rhodamine B solution.

[0142] Application Example 27

[0143] This application example is similar to application example 1, except that 0.02 g of the magnetic anchoring ternary composite magnetic material prepared in example 1 is replaced with 0.009 g of the nano zero-valent iron material of comparative example 2.

[0144] Application Example 28

[0145] This application example is similar to application example 27, except that the methyl orange solution is replaced by a rhodamine B solution.

[0146] Application Example 29

[0147] This application example is similar to application example 1, except that 0.02 g of the magnetic anchoring ternary composite magnetic material prepared in example 1 is replaced with 0.012 g of the Schiff base-zero-valent iron binary composite magnetic material of comparative example 3.

[0148] Application Example 30

[0149] This application example is similar to application example 29, except that the methyl orange solution is replaced by a rhodamine B solution.

[0150] like Figure 1 The figure shows a scanning electron microscope image of the nano-iron oxide material prepared in Example 1. Figure 1It can be seen that the morphology of nano-ferroferric oxide is nano-spherical, and the particle size distribution is about 20 nm, but the nano-ferroferric oxide particles show aggregation phenomenon, which is related to the strong magnetism of nano-ferroferric oxide. Agglomeration will have an adverse effect on the physical and chemical properties of nano-ferroferric oxide, and thus affect the application of nano-ferroferric oxide.

[0151] like Figure 2 The figure shows a scanning electron microscope image of the nano-iron tetroxide-Schiff base binary composite magnetic material prepared in Example 1. Figure 2 It can be seen that the nano-iron tetroxide-Schiff base binary composite magnetic material has a spherical core-shell structure, the outer layer is a micron-flaky Schiff base polymer, and the particle size distribution is close to about 3 microns, which is significantly larger than the particle size of nano-iron tetroxide, indicating that the Schiff base polymer is successfully coated on the outer surface of nano-iron tetroxide, and the increase in the particle size of the nano-iron tetroxide-Schiff base binary composite magnetic material is mainly attributed to the coated Schiff base polymer. In addition, it can be observed that some nano-iron tetroxide particles are distributed on the outer surface of the spherical core-shell structure, which may be attributed to the small amount of Schiff base polymer loaded by the reaction. However, if the loading amount of the Schiff base polymer is too much, the particle size and magnetism of the nano-iron tetroxide-Schiff base binary composite magnetic material will change significantly, which is not conducive to its potential application in water environment.

[0152] like Figure 3 The following is a scanning electron microscope image of the magnetic anchoring ternary composite magnetic material prepared in Example 1. Figure 3 It can be seen that the particle size of the magnetic anchored ternary composite magnetic material is larger than that of the nano-ferroferric oxide-Schiff base binary composite magnetic material, and the distribution of burr-type nano-spherical particles is observed on the outer surface of the magnetic anchored ternary composite magnetic material. These burr-type nano-spherical particles are evenly embedded on the outer surface of the spherical core-shell structure formed by the nano-ferroferric oxide-Schiff base binary composite magnetic material, and their particle size is roughly around 50 nm. Although the nano-zero-valent iron with a smaller particle size embedded on the outer surface of the spherical core-shell structure is not easy to observe due to the large overall particle size of the magnetic anchored ternary composite magnetic material, the burr-type nano-spherical particles distributed on the outer surface of the spherical core-shell structure indicate that the nano-zero-valent iron is magnetically anchored on the nano-ferroferric oxide-Schiff base binary composite magnetic material.

[0153] Combination Figure 1-3It can be seen that the microstructure of the magnetic anchoring ternary composite magnetic material prepared by the present invention is a spherical three-layer core-shell structure, which includes a central inner layer, an intermediate coating layer and an outer inlay layer from the inside to the outside, wherein the central inner layer is nano-ferroferric oxide, the intermediate coating layer is a micron-flaky Schiff base polymer, and the outer inlay layer is nano-zero-valent iron. Since both nano-ferroferric oxide and nano-zero-valent iron are magnetic, the nano-zero-valent iron in the outer inlay layer can be anchored on the outer surface of the nano-ferroferric oxide-Schiff base binary composite magnetic material by magnetic force, thereby making the Schiff base polymer in the intermediate coating layer and the nano-zero-valent iron in the outer inlay layer more firmly combined.

[0154] like Figure 4 , which is a scanning electron microscope image of the Schiff base-zero-valent iron binary composite magnetic material prepared in Comparative Example 3. Figure 4 It can be seen that the spherical nano zero-valent iron is dispersed and unevenly loaded on the micron-shaped Schiff base polymer, the loading between the Schiff base polymer and the nano zero-valent iron is not firm, and the Schiff base polymer and the nano zero-valent iron on the Schiff base-zero-valent iron binary composite magnetic material are easily separated and detached, which is not conducive to its potential water environment restoration and utilization. Compared with the Schiff base-zero-valent iron binary composite magnetic material, the microscopic morphology of the magnetic anchoring ternary composite magnetic material of the present invention has better integrity and homogeneity.

[0155] The magnetic anchoring ternary composite magnetic material prepared in Example 1 and the Schiff base-zero-valent iron binary composite magnetic material prepared in Comparative Example 3 were added to anhydrous ethanol to obtain a solution of the magnetic anchoring ternary composite magnetic material and a solution of the Schiff base-zero-valent iron binary composite magnetic material. Figure 5 As shown in the figure, it is a schematic diagram of magnetic separation of a solution of a magnetic anchoring type ternary composite magnetic material and a solution of a Schiff base-zero-valent iron binary composite magnetic material after ultrasonic treatment. It can be seen that after ultrasonic treatment for 30 s and magnetic separation, the transparency of the solution of the magnetic anchoring type ternary composite magnetic material and the solution of the Schiff base-zero-valent iron binary composite magnetic material show significant differences. After ultrasonic treatment and magnetic separation, the transparency of the solution of the magnetic anchoring type ternary composite magnetic material is higher than that of the solution of the Schiff base-zero-valent iron binary composite magnetic material, which indicates that the magnetic anchoring type ternary composite magnetic material has better stability, while the stability of the Schiff base-zero-valent iron binary composite magnetic material assembled by traditional micelle adsorption force in comparative example 3 is poor. The magnetic anchoring method described in the present invention can significantly improve the stability of the multi-component composite magnetic material, which will greatly expand the application prospects of the multi-component composite magnetic material in water treatment.

[0156] like Figure 6As shown, the removal performance of methyl orange by the magnetically anchored ternary composite magnetic material in application examples 1, 3, 5, 7, 9, 11, 13 and 15 are 57.52 mg / g, 52.36 mg / g, 48.32 mg / g, 45.1 mg / g, 35.31 mg / g, 26.79 mg / g, 30.19 mg / g and 25.92 mg / g, respectively. It can be seen that the removal performance of methyl orange by the magnetically anchored ternary composite magnetic material decreases with the decrease of the nano zero-valent iron loading, and the removal performance of methyl orange finally tends to be relatively stable, which indicates that the magnetically anchored ternary composite magnetic material has a good removal effect on methyl orange, and the magnetically anchored nano zero-valent iron has an important influence on the improvement of the removal performance of methyl orange. In addition, the removal performance of methyl orange by the magnetically anchored ternary composite magnetic material in Application Example 13 exceeds that in Application Example 11 and Application Example 15. This may be because the loading amount of nano zero-valent iron is too low, and its loading amount no longer has a significant effect on the removal performance of methyl orange, which leads to the difference in the removal performance of methyl orange.

[0157] like Figure 7As shown, the removal performance of methyl orange pollutants by the ternary composite magnetic materials prepared with different molar ratios of amine compounds, aldehyde compounds and nano-ferroferric oxide in Application Examples 1, 17, 19, 21, 23, 25, 27 and 29, the ternary composite magnetic materials prepared with different types of aldehyde compounds and amine compounds, the nano-ferroferric oxide-Schiff base binary composite magnetic materials, the nano zero-valent iron monomer materials and the nano zero-valent iron-Schiff base binary composite magnetic materials are 57.52 mg / g, 53.62 mg / g, 48.2 mg / g, 42.23 mg / g, 46.23 mg / g, 30.49 mg / g, 40.21 mg / g and 43.89 mg / g, respectively. It can be seen from application examples 1, 17 and 19 that the molar ratio of Schiff base polymer and nano zero-valent iron will affect the methyl orange removal performance of the magnetic anchoring ternary composite magnetic material. When the Schiff base polymer loading is high, the magnetic anchoring ternary composite magnetic material has better methyl orange removal performance, which is attributed to the Schiff base polymer providing some reactive sites for the adsorption and removal of organic dye pollutants. In addition, it can be seen from application examples 1, 21 and 23 that the removal performance of methyl orange by magnetic anchoring ternary composite magnetic materials prepared by different types of aldehyde compounds and amine compounds is different. The magnetic anchoring ternary composite magnetic material prepared by using o-toluidine and terephthalaldehyde has the best removal performance of methyl orange, which may be attributed to the fact that the terminal functional group types, overall molecular structure and carbon branched structure of diphenylamine and 4,4'-biphenyldicarboxaldehyde affect the degree of Schiff base polymerization reaction. In addition, it can be seen from Application Examples 1, 25, 27 and 29 that different types of binary composite magnetic materials and nano zero-valent iron have different removal performances for methyl orange. Application Example 25 is an experiment on the removal of methyl orange by the nano ferroferric oxide-Schiff base binary composite magnetic material prepared in Comparative Example 1. It can be seen that the removal performance of the nano ferroferric oxide-Schiff base binary composite magnetic material is lower than that of the magnetic anchoring ternary composite magnetic material prepared in Example 1. Application Example 27 is an experiment on the removal of methyl orange by the nano zero-valent iron material prepared in Comparative Example 2. It can be seen that nano zero-valent iron has good removal performance for methyl orange. Good removal performance, but its performance is lower than that of the magnetically anchored ternary composite magnetic material prepared in Example 1; Application Example 29 is a removal experiment of methyl orange by the Schiff base-zero-valent iron binary composite magnetic material prepared in Comparative Example 3. It can be seen that the removal performance of the Schiff base-zero-valent iron binary composite magnetic material for methyl orange is better than that of the nano-ferric oxide-Schiff base binary composite magnetic material and the nano-zero-valent iron material, but its performance is lower than that of the magnetically anchored ternary composite magnetic material in Example 1, which fully illustrates that the magnetically anchored ternary composite magnetic material prepared by the present invention has a better removal performance for methyl orange.

[0158] like Figure 8As shown, the removal performance of the magnetically anchored ternary composite magnetic material for Rhodamine B in Application Examples 2, 4, 6, 8, 10, 12, 14 and 16 are 22.26 mg / g, 18.86 mg / g, 17.25 mg / g, 15.46 mg / g, 14.86 mg / g, 14.26 mg / g, 10.56 mg / g and 14.06 mg / g, respectively. It can be seen that the removal performance of the magnetically anchored ternary composite magnetic material for Rhodamine B decreases with the decrease of the nano zero-valent iron loading amount, and the nano zero-valent iron anchored by magnetic force has an important influence on the improvement of the Rhodamine B removal performance. In addition, the removal performance of methyl orange by the magnetically anchored ternary composite magnetic material in Application Example 16 exceeds that of Application Example 14. This may be because the loading amount of nano zero-valent iron continues to decrease, and the loading amount of nano zero-valent iron on the magnetically anchored ternary composite magnetic material no longer has a significant effect on its removal performance of rhodamine B. Instead, the loaded nano zero-valent iron may affect the particle size and specific surface area of ​​the magnetically anchored ternary composite magnetic material.

[0159] like Fig. 9As shown, the removal performance of the rhodamine B pollutant by the ternary composite magnetic materials prepared with different molar ratios of amine compounds, aldehyde compounds and nano-ferroferric oxide in Application Examples 2, 18, 20, 22, 24, 26, 28 and 30, the ternary composite magnetic materials prepared with different types of aldehyde compounds and amine compounds, the nano-ferroferric oxide-Schiff base binary composite magnetic materials, the nano zero-valent iron monomer material and the nano zero-valent iron-Schiff base binary composite magnetic materials are 22.26 mg / g, 20.26 mg / g, 18.56 mg / g, 15.23 mg / g, 17.26 mg / g, 10.46 mg / g, 8.97 mg / g and 11.23 mg / g, respectively. It can be seen from Application Examples 2, 18 and 20 that the molar ratio of Schiff base polymer and nano zero-valent iron will affect the removal performance of the magnetic anchoring ternary composite magnetic material. When the Schiff base polymer loading is high, the magnetic anchoring ternary composite magnetic material has better Rhodamine B removal performance. In addition, it can be seen from Application Examples 2, 22 and 24 that the removal performance of Rhodamine B by magnetic anchoring ternary composite magnetic materials prepared from different types of aldehyde compounds and amine compounds is different, and the magnetic anchoring ternary composite magnetic material prepared from o-tolidine and terephthalaldehyde has the best removal performance for Rhodamine B. In addition, Application Example 26 is a removal experiment of rhodamine B by the nano-iron tetroxide-Schiff base binary composite magnetic material prepared in Comparative Example 1. It can be seen that the removal performance of the nano-iron tetroxide-Schiff base binary composite magnetic material is lower than that of the magnetic anchoring ternary composite magnetic material prepared in Example 1; Application Example 28 is a removal experiment of rhodamine B by the nano-zero-valent iron material prepared in Comparative Example 2. It can be seen that the nano-zero-valent iron has good removal performance for rhodamine B, but its performance is lower than that of the magnetic anchoring ternary composite magnetic material prepared in Example 1. Ternary composite magnetic material; Application Example 29 is an experiment on the removal of Rhodamine B by the Schiff base-zero-valent iron binary composite magnetic material prepared in Comparative Example 3. It can be seen that the removal performance of the Schiff base-zero-valent iron binary composite magnetic material for Rhodamine B is better than that of the nano-ferric oxide-Schiff base binary composite magnetic material and the nano-zero-valent iron material, but its performance is lower than that of the magnetically anchored ternary composite magnetic material of Example 1, which fully demonstrates that the magnetically anchored ternary composite magnetic material prepared by the present invention has excellent removal performance for Rhodamine B.

[0160] In summary, the magnetic anchoring ternary composite magnetic material prepared in Example 1 has the best removal performance for methyl orange and rhodamine B pollutants, which fully demonstrates the necessity of the magnetic anchoring modification reaction of the present invention. The magnetic anchoring ternary composite magnetic material of the present invention has good application prospects in removing organic dye pollutants.

Claims

1. Application of magnetic anchoring ternary composite magnetic material in removing organic dye pollutants from water, characterized in that: The microstructure of the magnetic anchoring ternary composite magnetic material is a spherical three-layer core-shell structure, which includes a central inner layer, an intermediate coating layer and an outer inlay layer from the inside to the outside, wherein the central inner layer is nano-ferroferric oxide, the intermediate coating layer is a micron-flaky Schiff base polymer, and the outer inlay layer is nano-zero-valent iron; the preparation method of the magnetic anchoring ternary composite magnetic material comprises the following steps: S1, dispersing nano-ferroferric oxide in ethanol to obtain a nano-ferroferric oxide dispersion; dissolving an amine compound in ethanol to obtain an amine solution; dissolving an aldehyde compound in ethanol to obtain an aldehyde solution; the amine compound is o-tolidine, and the aldehyde compound is terephthalaldehyde; S2, according to the molar ratio of amine compound, aldehyde compound and nano-ferroferric oxide being 1:1:(6-8), adding amine solution and aldehyde solution to nano-ferroferric oxide dispersion, reacting under stirring conditions, separating precipitate after the reaction, washing and drying to obtain nano-ferroferric oxide-Schiff base binary composite magnetic material; S3, dispersing nano-ferroferric oxide-Schiff base binary composite magnetic material in ethanol to obtain a binary composite magnetic material solution; dispersing nano-zero-valent iron in ethanol to obtain a nano-zero-valent iron solution; adding the nano-zero-valent iron solution dropwise into the binary composite magnetic material solution under stirring conditions, and after continuous stirring, separating the precipitate, washing and drying, to obtain a magnetically anchored ternary composite magnetic material; wherein the mass ratio of nano-ferroferric oxide-Schiff base binary composite magnetic material to nano-zero-valent iron is (0.18-0.11):(0.02 -0.09).

2. The use of the magnetic anchoring ternary composite magnetic material according to claim 1 in removing organic dye pollutants in water bodies is characterized in that: In S1, the preparation method of nano-iron tetroxide comprises: dissolving FeCl3 in a mixed solution of water, ethanol, n-hexane and oleic acid, and reacting under stirring conditions; adding sodium hydroxide to the obtained reaction solution, reacting under heating and stirring conditions, separating the liquids after the reaction is completed, washing and drying the organic layer obtained by the separation to obtain an organic mixture; dispersing the organic mixture in a mixed solvent of oleic acid and 1-octadecene, reacting under a nitrogen atmosphere and heating conditions, and washing and drying after the reaction is completed to obtain nano-iron tetroxide.

3. The use of the magnetic anchoring ternary composite magnetic material according to claim 1 in removing organic dye pollutants in water bodies is characterized in that: In S3, the preparation method of nano zero-valent iron comprises: dissolving ferric chloride in a mixed solution of ethanol and water, then dropping a potassium borohydride solution into the mixed solution, reacting under stirring conditions, and after the reaction is completed, separating the precipitate and washing and drying it to obtain nano zero-valent iron.

4. The use of the magnetic anchoring ternary composite magnetic material according to claim 1 in removing organic dye pollutants in water bodies is characterized in that: In S3, stirring is performed under anaerobic conditions.

5. The use of the magnetic anchoring ternary composite magnetic material according to claim 1 in removing organic dye pollutants in water bodies, characterized in that: In S3, the separating of the precipitate is specifically carried out by using a magnetic separation method to separate the precipitate.

Citation Information

Patent Citations

  • Nanometer ferroferric oxide core-carbon meso pore hollow shell complex, as well as preparation method and application thereof

    CN102649046A

  • Powdery vanillic aldehyde modified chitosan Schiff base decolorizing agent and preparation method thereof

    CN112619613A

  • Schiff base nano zero-valent iron composite magnetic material as well as preparation method and application thereof

    CN118231127A